1999
DOI: 10.1007/s002239900622
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density, Vitamin D Status, and Disordered Bone Remodeling in End-Stage Chronic Liver Disease

Abstract: Hepatic osteodystrophy occurs in up to 50% of patients with chronic liver disease (CLD). The aim of this study was to determine the relative contribution of increased resorption and decreased formation to hepatic osteodystrophy by measuring biochemical markers. Twenty-seven patients with advanced CLD (14 female, 13 male) were enrolled. Bone mineral density (BMD), measured at the lumbar spine, and femoral neck, were measured by dual energy X-ray absorptiometry (DXA); bone turnover was assessed using biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…Indeed, Long et al (23) and Crosbie et al (26) reported that treatment with vitamin D does not prevent the progression of hepatic osteodystrophy in adults. The present study shows that children and adolescents with CCD have a significant limitation of bone mass development even when their serum 25-OH-D levels are maintained within normal limits.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Long et al (23) and Crosbie et al (26) reported that treatment with vitamin D does not prevent the progression of hepatic osteodystrophy in adults. The present study shows that children and adolescents with CCD have a significant limitation of bone mass development even when their serum 25-OH-D levels are maintained within normal limits.…”
Section: Discussionmentioning
confidence: 99%
“…A SD of 0.061 g/cm 2 for BMD over 1 year was estimated from the literature. 8,13,31 An expected improvement of 0.04 g/cm 2 in BMD over 1 year in the treated group and an expected deterioration of Ϫ0.02 g/cm 2 in the placebo group were assumed. Based on these assumptions, a total sample size of 34 (17 patients per group) would provide 80% power to detect a significant difference (0.06 g/cm 2 ) at 1 year between the BMD change from baseline in the treated group and the BMD change in the placebo group.…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…6 Increased bone resorption has also been suggested as a contributing mechanism in PBC-related bone disease, as elevations in serum and urinary markers of bone resorption have been found in these patients. 7,8 No specific therapy for PBC-related bone loss has been definitely established. Ursodeoxycholic acid is of no benefit on the BMD of patients with PBC.…”
mentioning
confidence: 99%
“…Although this may occur in patients with chronic liver disease, it is rare. 52 Conversely vitamin D insufficiency, in which lesser degrees of deficiency result in secondary hyperparathyroidism and bone loss, 53 is commonly associated with chronic liver disease 50,51,54,55 and may contribute to post-transplantation osteoporosis. Prospective studies indicate that serum 25-hydroxyvitamin D levels, which reflect vitamin D status, tend to increase with time after transplantation, 15,23,33 and in the study of Feller et al 27 significantly higher serum 25-hydroxyvitamin D levels were noted at a mean of 85 months follow-up than prior to transplantation; however, serum 1,25-dihydroxyvitamin D levels, which were normal at baseline, did not change during the follow-up period.…”
Section: Vitamin D Deficiency/insufficiencymentioning
confidence: 99%
“…Thus in some studies, the changes were predominantly those of low bone turnover and reduced bone formation at the cellular level, 30,59,60 whilst others have also reported evidence of increased turnover and resorption. [61][62][63][64] Biochemical markers of bone formation have been reported to be decreased 51 or normal 55 and resorption markers increased. 51,55 The heterogeneity observed in the histological characteristics is likely to reflect a number of factors including differences in the underlying liver disease and its severity, the prevalence of vitamin D deficiency and secondary hyperparathyroidism, and the presence or absence of glucocorticoid therapy.…”
Section: Pre-existing Bone Diseasementioning
confidence: 99%